The Effectiveness of the Emotional Control Card Technique in Group Counseling to Reduce Anxiety in College Students STKIP Tulungagung - Izati, Maydana; Hambali, IM; Chusniyah, Tutut (Jurnal Sains Psikologi, 2023)
This study is based on the phenomenon of anxiety level experienced by students in the learning process. This research uses pretest-postest control group design research design. Subjects in this study amounted to 40 students consisting of 20 students into experimental groups and 20 students into a control group. This research uses data analysis with t test gain score independent sample test. Results from this study that the experimental group lower the anxiety level than the control group and the technique of Emotional Control Card is effective in reducing students' anxiety.